PERSPECTIVE AREAS AND DIRECTIONS OF DEVELOPMENT OF THE UKRAINE TOURIST SECTOR WITH THE APPLICATION OF MODERN MARKETING TOOLS - PANCHENKO, VOLODYMYR; BARAN, ROSTYSLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article summarizes the features of world tourism development in the context of strengthening globalization processes. It is determined that in the conditions of globalization tourist enterprises should not only improve the existing components of the marketing complex, but also look for innovative areas of strategic development of the effectiveness of the management of the Internet marketing system. The perspective spheres and directions of development of the system of Internet marketing of the enterprises of tourism of Ukraine are systematized. The influence of the development of digital technologies and the COVID-19 pandemic on the transformation of the marketing concept of the tourist product of Ukraine is substantiated. Priority areas for reorientation of the Internet marketing system of tourist enterprises have been identified. The priority directions of development of communication strategy of the system of internet marketing of tourist enterprises are offered. Innovative spheres of development of the system of Internet marketing of tourist enterprises are conceptualized. Among the most important are: development of innovative tourist products; complex and constant integration of innovative technological developments into the value chain; reorientation from e-commerce to m-commerce; development of own online platforms and use of created and offered by world and regional providers – market leaders; development of contextual and targeted Internet advertising; ensuring the development of infrastructure and speed of e-marketing and m-marketing; improving the tools of messenger marketing and promotion on social networks; formation of business metrics; introduction of omnichannel communication; development of competencies and experience of consumers; building communities of participants in the tourism process; clear CRI for internet marketing system.
Keywords: innovative development; tourist enterprise; globalization processes; world tourism; tourist services; specialization of the tourist market